Molecular dynamics study of the penetration resistance of multilayer polymer/ceramic nanocomposites under supersonic projectile impacts. (April 2021) - Dewapriya, M.A.N.; Miller, R.E.
Abstract: We simulated ballistic impact tests of multilayer polyurea/silicon-carbide (SiC) nanostructures using molecular dynamics (MD). First, we conducted density functional theory calculations to obtain accurate parameters to model the nonbonded interactions of the polyurea/SiC interface and subsequently investigated the influence of interfacial adhesion on the impact response. Our MD simulations demonstrate that the ballistic limit velocity and the specific penetration energy of the polyurea/SiC multilayers are significantly higher than the experimentally measured values of other protective materials. Moreover, we demonstrated that the specific penetration energy of a nanoscale target with a given material composition can be remarkably improved (over 75%) by optimizing the individual layer thickness and their arrangement within the target. Our results reveal a potential bottom-up design pathway for developing superior protective materials for extreme engineering applications.